2022
DOI: 10.1002/admi.202200260
|View full text |Cite
|
Sign up to set email alerts
|

BiOX/Bi/BiOX (X = Cl, Br) Double‐Side Nanosheet Arrays: Synthesis, Structures, and Photo(electro)catalytic Applications

Abstract: Array‐structured photocatalysts, featuring unique transport properties of charge carriers and special texture structures, have captured widespread interest in photocatalytic and/or photoelectrocatalytic applications. However, the fabrication of arrays usually suffers from complicated synthetic routes and the indispensable use of substrates. Herein, a novel BiOX/Bi/BiOX (X = Cl, Br) double‐side nanosheet array catalyst, with vertically aligned BiOX nanosheets symmetrically grown on the two sides of horizontal B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 51 publications
(71 reference statements)
5
11
0
Order By: Relevance
“…Overall, l -Cys as a structure-directing reagent can adjust the morphology of materials. When the amount of l -Cys was less, the BiO X /Bi/BiO X ( X = Cl, Br) double-sided nanosheets were formed (shown in Figure S3), whose growth mechanism has been explored in our previous report . More specially, in the present study, when the amount of l -Cys was increased, the pine dendritic nanoassembly structure can be obtained.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Overall, l -Cys as a structure-directing reagent can adjust the morphology of materials. When the amount of l -Cys was less, the BiO X /Bi/BiO X ( X = Cl, Br) double-sided nanosheets were formed (shown in Figure S3), whose growth mechanism has been explored in our previous report . More specially, in the present study, when the amount of l -Cys was increased, the pine dendritic nanoassembly structure can be obtained.…”
Section: Resultssupporting
confidence: 62%
“…Following the same synthesis steps, the Bi/BiOCl sample was obtained using KCl as a raw material. As a comparison, the spherical Bi/BiOBr and lamellar BiOBr were synthesized according to the experimental steps in the report. , The morphologies of spherical Bi/BiOBr and lamellar BiOBr are shown in Figure S1.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many inorganic Bi-containing compounds such as Bi 2 O 3 , BiOX (X = Cl, Br, I), Bi 2 MoO 6 , BiVO 4 and so on due to narrow band gaps, low toxicity, good environmental acceptability and low price be widely used in the eld of photochemical technique. [14][15][16][17][18][19] In 1999, Kudo et al reported that the bismuth tungsten showed photocatalytic activity under the visible light irradiation. [20] Although it has the above advantages, in recent years, compounds contain covalent organic moiety are still seldom used as photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The [Bi 2 O 2 ] 2+ and [Br − ] are perpendicular to the internal electric field, which facilitates the separation of photon‐generated carriers. [ 18 ] BiOBr is also an indirect transition semiconductor, which facilitates the reduction of the probability of electron–hole recombination. Based on the above discussion, BiOBr is considered as a potential photocatalyst for photocatalytic N 2 fixation.…”
Section: Introductionmentioning
confidence: 99%